Counseling and Christianity five approaches - Greggo, Stephen P., 1956-; Sisemore, Timothy A. (Downers Grove, Ill. : IVP Academic, 2012)
This volume explores how five major perspectives on the interface of Christianity and psychology would each actually be applied in a clinical setting. Respected experts associated with each of the perspectives depict how to assess, conceptualize, counsel and offer aftercare to Jake, a hypothetical client with a variety of complex issues. In each case the contributors seek to explain how theory can translate into real-life counseling scenarios. --from publisher description
Setting the stage for the five approaches -- Moving models into practice -- A levels-of-explanation approach / Thomas G. Plante -- An integration approach / Mark McMinn -- A Christian psychology approach / Diane Langberg -- A transformational approach / Gary Moon -- A biblical counseling approach / Stuart W. Scott -- Distinctives and dialogue -- Conceptualization and contextualization -- Case studies for further exploration.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Counseling -- Religious aspects -- Christianity; RELIGION / Christian Ministry / Counseling & Recovery; Electronic books